Analisis Faktor-Faktor Yang Mempengaruhi Minat Beli Konsumen Terhadap Produk Skincare X: Studi Pada Pengguna Platform Y Generasi Z - Mohamad Badar Fadlilah; Ryna Parlyna; Inkreswari Retno Hardini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effects of perceived quality, online customer reviews, and influencer characteristics including trustworthiness, expertise, and attractiveness on skincare purchase intention among digital consumers. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS. The research respondents consist of 302 individuals aged 18–28 years who actively seek skincare information through digital media, selected using a purposive sampling technique, with a research instrument comprising 30 statement items. The results indicate that perceived quality, expertise, and attractiveness have a positive and significant effect on purchase intention, while trustworthiness has no significant effect. In addition, online customer reviews show a significant negative effect, indicating that biased online reviews can reduce purchase intention. As a practical implication, the findings of this study are implemented in an artificial intelligence-based application prototype named SKINLYTIC, which serves as a decision support system to facilitate more rational and informed skincare purchase decisions.